2022
DOI: 10.3389/fenvs.2022.813347
|View full text |Cite
|
Sign up to set email alerts
|

Does the E-Commerce City Pilot Reduce Environmental Pollution? Evidence From 265 Cities in China

Abstract: In order to promote the healthy and rapid development of e-commerce, China launched the construction of National E-commerce Demonstration Cities in 2009. This paper presents a feasible road to achieving sustainable development through the new urban development model. The paper employs the data of 265 cities in China from 2007 to 2016 as a research sample and uses the multiperiod difference-in-difference method to test the impact of National E-commerce Demonstration Cities pilots on urban environmental pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The second factor accounted for 31.73% of the total variance for particulate-phase PAHs, and Phen and Pyr were dominant, which may have been emitted from diesel sources. The results obtained from PC-2 demonstrated that the low molecular weight (Phen) indicated a petrochemical source (77,78). For the third factor, high molecular weight PAHs [B(b)F, B(a)P, and DahA] were dominant components, which accounted for 26.5% of the total variance for particulate-phase PAHs.…”
Section: Pca For Seasonal Pahsmentioning
confidence: 97%
“…The second factor accounted for 31.73% of the total variance for particulate-phase PAHs, and Phen and Pyr were dominant, which may have been emitted from diesel sources. The results obtained from PC-2 demonstrated that the low molecular weight (Phen) indicated a petrochemical source (77,78). For the third factor, high molecular weight PAHs [B(b)F, B(a)P, and DahA] were dominant components, which accounted for 26.5% of the total variance for particulate-phase PAHs.…”
Section: Pca For Seasonal Pahsmentioning
confidence: 97%
“…E-commerce has a strong radiation effect and spatial spillover effect. Through cluster effects, carbon emissions have been reduced [ 14 , 15 ], agricultural pollution has been alleviated [ 16 , 17 ], agricultural technological innovation has been promoted [ 18 , 19 ], and agricultural factor input efficiency has been improved [ 14 ]. The development of agricultural e-commerce will actively promote the upgrading and high-quality development of agricultural industry [ 4 , 20 , 21 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of e-commerce has a positive impact on carbon emissions [ 42 , 43 ], agricultural ecological environment [ 16 , 17 ], and green innovation development [ 14 , 18 ]. However, due to the "endogenous" nature of E-commerce technology, existing research is mainly limited to its role in promoting the development of rural industries [ 4 , 44 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To alleviate endogeneity problems, this paper conducts research using the instrumental variable ( IV ) approach. For the assortment of the instrumental variable, refer to the research ideas as discussed by Zhang et al ( 78 ). Ming Dynasty post stations were the national postal and postal transportation system in ancient times.…”
Section: Empirical Analysismentioning
confidence: 99%